1991
DOI: 10.1111/j.1600-0838.1991.tb00302.x
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal symptoms during endurance running

Abstract: intestinal symptoms during endurance running. Scand J Med Sci Sports 1991: 1: 232-234.The incidence and type of gastrointestinal complaints among endurance runners were investigated with a questionnaire among participants in a marathon event in northern Finland. The running distances were %, % and full marathon. The fitness level of the participants varied from habitual joggers to national-class endurance runners. The response rate of the 426 participants was 55% (230). Gastrointestinal disturbances during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Therefore, the subjects in this study may not have reported less intense experiences of ETAP. Smaller studies have reported the incidence of ETAP to be 21 % for a 10-km event [ 15 ] and 19 % for a 67-km ultramarathon [ 4 ]. Hence, the body of evidence suggests that approximately one in five participants in a running event may be expected to experience ETAP.…”
Section: Prevalence and Incidence Of Exercise-related Transient Abdommentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, the subjects in this study may not have reported less intense experiences of ETAP. Smaller studies have reported the incidence of ETAP to be 21 % for a 10-km event [ 15 ] and 19 % for a 67-km ultramarathon [ 4 ]. Hence, the body of evidence suggests that approximately one in five participants in a running event may be expected to experience ETAP.…”
Section: Prevalence and Incidence Of Exercise-related Transient Abdommentioning
confidence: 99%
“…A high level of physical conditioning may decrease the experience of ETAP [ 2 , 3 ]; however, the ailment is not unknown among well trained and even elite athletes [ 10 , 12 , 15 ]. Morton and Callister [ 1 ] observed well conditioned individuals to be as likely to report experiencing ETAP within the past year as less conditioned individuals and also to report pain of a similar severity, although better conditioned individuals reported experiencing the pain less frequently.…”
Section: Factors Influencing the Experience Of Etapmentioning
confidence: 99%
See 3 more Smart Citations